Comprehensive management of patients with pelvis organ prolapse and metabolic syndrome - Irina A. Lapina (IP Berlin A.V., 2021)
Background. Genital prolapse (GP) and stress urinary incontinence (SUI) are characterized by a failure of connective tissue skeleton of the pelvic floor structures, and there are many risk factors in their pathogenesis. Metabolic syndrome (MS), which includes obesity and abnormalities in the lipid and carbohydrate profile, contributes to the initiation of pelvic organ prolapse (POP) due to increased intra-abdominal pressure and the presence of comorbidities. Endothelial dysfunction associated with MS aggravates the existing metabolic disorders, resulting in the formation of a vicious circle and an increase in the likelihood of recurrence of genital prolapse symptoms and НМ during tension in the postoperative period.